Treatment outcome of acromegaly due to pituitary macroadenoma in a single tertiary centre - R, Subashini; L, Huai Heng; WS, Wan Juani; M , Azura Dina; Shahar, Mohammad Arif; O, Mohd Rahman; Omar, Ahmad Marzuki; Wahab, Norasyikin; Sukor, Norlela; Mustaffa, Norlaila; Zainuddin, Suehazlyn; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)

(untitled)
Introduction: Acromegaly, primarily due to a growth hormone (GH) producing pituitary macroadenoma may require several modalities of treatment to control the disease. As surgery is curable in about half of the cases, most patients require medical or radiation therapy in addition to surgery. Method: A retrospective descriptive study of acromegaly patients in University Kebangsaan Malaysia Medical Centre from the year of 2000 to 2014. Results: There was 14 acromegaly patients due to pituitary macroadenoma, comprising 10 males and 4 females. The mean age at diagnosis was 44.29 ± 10.16 years. Majority were Malays (64%), followed by 29% Chinese and the remaining 7% were Indians. Hypertension was the most common co-morbid (n=11), followed by diabetes (n=7), dyslipidemia (n=5), hypopituitarism (n=4) , sleep apnea and arthralgia, 3 patients each. Mean duration of illness was 13 ± 7 years. Mean IGF-1levels was 815.91 ± 119.58 ng/ml. Modalities of treatment included, surgery followed by medical treatment (n=6), medical treatment alone (n=6) and one had surgery only. One patient refused any form of treatment. The number of patients who received somatostatin analog (SA) was 7, whereby 2 patients received SA following surgery. Ten patients received dopaminergic agonist (DA) and 6 of them were after surgery. Overall response rate was 57% (n=8) of patients based on normalization of IGF-1 levels for age and sex. The mean IGF-1 amongst the responders was 167.25 ± 92.74 ng/ml. Five of them required combination of pituitary surgery and medication, either DA and/or SA. Two patients responded with medical treatment alone and one with surgical treatment alone. Discussion: Eighty three percent achieved response from surgical followed by medical treatment and 33% from medical therapy alone. Biochemical control with octreotide LAR as adjunct to surgery based on IGF-1 criteria was 67% in a study by Freda et all.1 Primary octreotide LAR and primary cabergoline treatment resulted in normalization of IGF-1 in 34% and 20- 33% respectively, which is consistent with our findings.2-3Addition of DA has shown to help 42% to achieve normal IGF-1 levels4. Despite the insignificant difference in view of the small sample size in our study, more patients went into remission with combination therapy. Conclusion: Up to 83% of patients who had residual disease post surgery achieved control with the use of medical therapy compared to monotherapy. 1 Freda PU, Katznelson L, van der Lely AJ, Reyes CM, Zhao S, Rabinowitz D. Long-acting somatostatin analog therapy of acromegaly: a metaanalysis. J Clin Endocrinol Metab. 2005;90(8): 4465–4473. 2Mercado M, Borges F, Bouterfa H, et al. A prospective, multi- centre study to investigate the efficacy, safety and tolerability of octreotide LAR (long-acting repeatable octreotide) in the primary therapy of patients with acromegaly. Clin Endocrinol (Oxf). 2007;66(6):859–868. 3 Sandret L, Maison P, Chanson P. Place of cabergoline in acromegaly: a meta-analysis. J Clin Endocrinol Metab. 2011;96(5): 1327–1335. 4Cozzi R, Attanasio R, Lodrini S, Lasio G. Cabergoline addition to depot somatostatin analogues in resistant acromegalic patients: efficacy and lack of predictive value of prolactin status. Clin Endocrinol (Oxf). 2004;61:209- 215.